A Computer-Based Touch-Less 3D Controller Using Capacitive Sensing Method - Nur Shazwani, Aminuddin; Syafeeza, Ahmad Radzi; M., Abu; Norihan, Abdul Hamid (Penerbit Universiti, UTeM, 2016)
This paper focuses on the application of touch-less interaction between human and computer using capacitive sensing technique. A computer–based analysis for touch-less 3D controller using capacitive sensing method in [1] is developed. In this project, Arduino UNO is used as a microcontroller to bridge the interface connection between the sensor hardware and the computer. This method uses capacitive based sensor as the main component to sense the gesture movement near it. The capacitive based sensing depends on the duration to charge a capacitor (known as the time constant). By placing an object within the electric field of a capacitor, it will immediately affect the capacitance value and it will correspond to the time constant. In the final analysis, the touch-less hardware will be linked to MATLAB software to study its characteristic and behavior. Using the data obtained from the analysis, a touch-less control from the hardware will control the computer keyboard. To show its additional functionality, a Google Earth program will display the ability of the touch-less interface.